β-decay half-lives of neutron-rich nuclei around 158Nd, relevant to the formation of the A≈165 rare-earth element peak - Wu J.; Nishimura S.; Lorusso G.; Xu Z.Y.; Ideguchi E; Simpson G.S.; Baba H.; Browne F.; Daido R.; Doornebal P.; Fang Y.F.; Isobe T.; et al. (EPJ Web of Conferences, 2016)
A β-decay spectroscopy experiment around 158Nd was performed at RI Beam Factory (RIBF), RIKEN Nishina Center, in order to understand the production mechanism of the A≈165 rare-earth element (REE) peak in the r-process mass abundance pattern. In this experiment, 53 half-lives are measured including 34 new results, which could be employed in a fully dynamic r-process network calculation.